Three new masdevallia species (orchidaceae: pleurothallidinae) from Peru - Dalström, Stig (Universidad de Costa Rica, 2014)
Three new Masdevallia species are described, illustrated and compared with similar species. A brief taxonomic discussion is held about the justification for describing the new taxa as Masdevallia and not as belonging to any of the recently proposed segregated genera. The first species is most similar to M. rimarima- alba but differs in having a more tubular flower and a narrower lip, the second species is similar to M. dudleyi and M. nunezii but differs in the richly pubescent sepals, and the third species is distinguished from other similar and multiflowered Masdevallia species by the rugose lip.